2008
DOI: 10.1089/ars.2007.1855
|View full text |Cite
|
Sign up to set email alerts
|

The Machinery for Oxidative Protein Folding in Thermophiles

Abstract: Disulfide bonds are required for the stability and function of many proteins. A large number of thiol-disulfide oxidoreductases, belonging to the thioredoxin superfamily, catalyze protein disulfide bond formation in all living cells, from bacteria to humans. The protein disulfide isomerase (PDI) is the eukaryotic factor that catalyzes oxidative protein folding in the endoplasmic reticulum; by contrast, in prokaryotes, a family of disulfide bond (Dsb) proteins have an equivalent outcome in the bacterial peripla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 112 publications
(121 reference statements)
0
14
0
Order By: Relevance
“…As such, the induction of bcp4 (Msed_0359) by HD Co 2ϩ and by LD and HD Zn 2ϩ suggests that metal shock triggered endogenous oxidative stress. Also in S. solfataricus, PDO is the substrate of thioredoxin reductase and plays a central role in the biochemistry of cytoplasmic disulfide bonds (34). Exposure to HD Co 2ϩ , Cu 2ϩ , and Zn 2ϩ induced PDO in M. sedula, implying that these metals impacted disulfide bonds and/or their formation.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the induction of bcp4 (Msed_0359) by HD Co 2ϩ and by LD and HD Zn 2ϩ suggests that metal shock triggered endogenous oxidative stress. Also in S. solfataricus, PDO is the substrate of thioredoxin reductase and plays a central role in the biochemistry of cytoplasmic disulfide bonds (34). Exposure to HD Co 2ϩ , Cu 2ϩ , and Zn 2ϩ induced PDO in M. sedula, implying that these metals impacted disulfide bonds and/or their formation.…”
Section: Resultsmentioning
confidence: 99%
“…Disulfide bond formation is catalyzed by thioredoxin-like proteins in non-reducing compartments like the eukaryotic endoplasmic reticulum, the inner membrane space of mitochondria, and the periplasm of Gram-negative bacteria (13). The protein-disulfide isomerase was the first disulfide bondforming enzyme discovered by Anfinsen and colleagues (14,15) that contains two redox-active CXXC motifs.…”
Section: The Atomic Coordinates and Structure Factors (Code 4z7x) Havmentioning
confidence: 99%
“…Structural Cys are often used in secreted proteins and those located in oxidizing environments, such as bacterial periplasm and eukaryotic endoplasmic reticulum (ER), but are much less frequent in reducing environments (e.g., cytosol, nucleus and mitochondrial matrix). However, in some thermophilic bacteria, structure stabilization through disulfide bonds is used even for cytosolic proteins (75). Many computational and experimental studies revealed that disulfide bridges can increase conformational stability of proteins, mainly by reducing the conformational entropy of the unfolded state and constraining the unfolded conformation (1,5,85).…”
Section: Structural Disulfidesmentioning
confidence: 99%